THE SEARCH FOR SELF-IDENTITY IN EBERSHOFF’S THE DANISH GIRL - Ngongoloy, Elisia Nicolin; Ceisy N. Wuntu,; Delli Sabudu, (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
Humans typically are born as either men or females, with their own body parts and reproductive organs. But there are some cases where people experience confusion or uncertainty about their gender identity. This research categorized as qualitative research. The Psychoanalysis by Freud based on the three fundamental components: the id, ego, and superego is used to analyzed the data. It is revealed that as he searches for his true identity in a way that he tries to behave as a woman, has an attraction to men that should be done by women, wears women's clothes, and finally performs sex reassignment surgery to become a woman. Although he decided to change his identity as a woman, his wife Gerda still accepted, cared for and helped him at that time. Einar was happy with his new life, despite many obstacles and eventually died after undergoing surgery during his self-discovery process.